Penerapan Konsep Ash-Shiddiq Pedagang Temporer pada Wisata Mappogau Sihanua di Kabupaten Sinjai - Darnayanti Darnayanti; Irwan Misbach; Wahid Haddade (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
The dependency between a human with another human cannot be denied anymore so that it's needed a collaboration to fulfil their life based on Islam recommendation. A good Muslim is who does work that not conflict with Islamic law. Since the birth of Islam, trading has been known as a lines of fulfilling the necessities of life which is halal and recommended. The same thing happened at Tompobulu village, Bulupoddo, Sinjai where the temporary traders appeared at the certain time in a traditional party held